How common is intestinal parasitism in HIV-infected patients in Malaysia? - Asma, I.; Johari, Surin; Sim, Benedict Lim Heng; Lim, Yvonne Ai Lian (Malaysian Society of Parasitology and Tropical Medicine, 2011)
Human immunodeficiency virus (HIV)-infected individuals have greater susceptibility to infections by a myriad of microorganisms which can cause significant morbidity and mortality compared to immunocompetent individuals. Of these microbial infections, intestinal parasitic infections (IPIs) however are receiving less attention than bacterial and viral infections, hence, the lack of information of parasitic infections in HIV individuals. Prevalence of IPIs among 346 HIV-infected individuals in Malaysia was determined in this study. The overall prevalence of intestinal parasitic infections (IPIs) was 37.9% (131 of 346) with protozoa infections (18.8%) being more common compared to helminth infections (7.5%). Observed protozoa include Entamoeba histolytica/dispar (16.8%), Cryptosporidium parvum (12.4%), Isospora belli (10.1%), Cyclospora cayetanensis (4.9%) and Giardia duodenalis (intestinalis) (3.2%) whilst helminthes which were detected comprised of Ascaris lumbricoides (13.9%), Trichuris trichiura (6.4%) and hookworms (0.6%). Among those 131 infected, 50.4% had multiple infections and 48.9% had single parasitic infection. The CD4 counts were significantly lower (i.e., 200 cells/mm3) in patients harbouring IPIs. Of those individuals infected with intestinal parasites, 49% were intravenous drug users and 58% were not on any antiretroviral therapy. Most were asymptomatic and had concurrent opportunistic infections (OIs) mainly with Mycobacterium tuberculosis infection. These results confirmed that IPIs are ubiquitous among HIV-infected individuals, especially those presenting with low CD4 T cells counts, and provide useful insights into the epidemiology of these infections among HIVinfected patients in Malaysia. It is therefore recommended, that diagnosis of these intestinal parasitic pathogens should be conducted on a routine basis for better management of gastrointestinal illnesses among HIV individuals.